A Systematic Review of Medical Equipment Reliability Assessment in Improving the Quality of Healthcare Services - Aizat Hilmi Zamzam; Ahmad Khairi Abdul Wahab; Suresh Chandra Satapathy; Khin Wee Lai; Khairunnisa Hasikin; Muhammad Mokhzaini Azizan (Frontiers Media S.A, 2024)
Indexed by WOS/Scopus/ERA